Bronchial Epithelial Cells from Cystic Fibrosis Patients Express a Specific Long Non-coding RNA Signature upon Pseudomonas aeruginosa Infection - Balloy, Viviane; Koshy, Remya; Perra, Lea; Corvol, Harriet; Chignard, Michel; Guillot, Loïc; Scaria, Vinod (Frontiers in Cellular and Infection Microbiology, 2017)
Pseudomonas aeruginosa (Pa) is the leading cause of chronic lung infection in Cystic Fibrosis (CF) patients. It is well recognized that CF epithelial cells fail to develop an appropriate response to infection, allowing bacterial colonization and a chronic inflammatory response. Since long non-coding RNAs (lncRNAs), are known to play a key role in regulating mammalian innate immune response, we hypothesized that CF cells exposed to Pa could express a specific lncRNA signature responsible of the maladaptative CF response. We analysed transcriptomic datasets to compare the expression profiles of lncRNAs in primary CF and non CF epithelial cells infected with Pa at 0, 2, 4 and 6 hours of infection. Our analysis identified temporal expression signatures of 25, 73, 15 and 26 lncRNA transcripts differentially expressed at 0, 2, 4 and 6 h post-infection respectively, between CF and non CF cells. In addition, we identified profiles specific to CF and non CF cells. The differential expression of two candidate lncRNAs were independently validated using real-time PCR. We identified a specific CF signature of lncRNA expression in a context of Pa infection that could potentially play a role in the maladaptive immune response of CF patients.